Optimization of Air Demand Rate in Water Jet Aerators - Ozkan, Fahri; Onay, Begum Kantarci; Aydin, Alp Bugra; Arici, Erdinc (Springer Int Publ Ag, 2022)
Water jets are one of the pressurized flow systems that are used to increase the dissolved oxygen value in the water and have high aeration efficiency. In this widely used system, it is of great importance to determine the effect rates of the factors that affect the air transfer efficiency. Therefore, in this study, the factors affecting the air transfer efficiency of water jets were analyzed by Taguchi method. Taguchi orthogonal array was used to determine the number of necessary experiments. For this purpose, four-parameter L18 (6(1) x 3(3)) orthogonal array was chosen. The Reynold number from these parameters is six levels, the air hole diameter, the pipe length and the impact distance are three levels. Analysis of experimental data was performed by Taguchi method. The analyses results were used to determine the optimum parameter levels. The confirmation test was performed according to the optimum levels, and the experimental results were compared with the results of the analysis. In addition, ANOVA (Variance) analysis was performed to determine the effects of parameters on air demand ratio. As a result, it was determined that the most effective factors on the air demand ratio were pipe length and impact distance, respectively.
Keywords: Air demand rate; Water jet; Taguchi method; Optimization; Aeration